Adhesive behaviour and virulence of coagulase negative staphylococci isolated from Italian cheeses. (September 2015) - Artini, Marco; Cellini, Andrea; Papa, Rosanna; Tilotta, Marco; Scoarughi, Gian Luca; Gazzola, Simona; Fontana, Cecilia; Tempera, Gianna; Cocconcelli, Pier Sandro; Selan, Laura
Coagulase-negative staphylococci (CoNS) belong to saprophytic microbiota on the skin and mucous membranes of warm-blooded animals and humans, but are also isolated from foodstuffs such as meat, cheese, and milk. In other circumstances, some CoNS can act as pathogens. Thus the presence of CoNS may not be an immediate danger to public health, but can become a risk factor. In particular antibiotic-resistant genes could be transferred to other potentially pathogenic microorganisms. Furthermore, CoNS are known to be strong biofilm producers and this is also a risk factor for public health. The aim of the present work was to determine the genotypic and phenotypic profiles of 106 CoNS belonging to four different species isolated from five different Italian cheeses for the presence of some adhesion and virulence features. In order to verify a possible correlation between the formation of biofilm and staphylococcal virulence factors, we checked the presence of adhesin genes by PCR and we investigated the ability of these strains to make biofilm at different temperatures. Furthermore, in some conditions, we analyzed surface proteins and autolytic pattern of selected strains. In conclusion, we checked the presence of norA and mecA genes responsible for fluoroquinolones and methicillin resistance, respectively. We found resistant genes in a proportion of the food isolates in amounts of 9.4% ( mecA ) and 5.7% ( norA ). These data support the importance to continuously examine the microbiota not only for the creation of a database but also to safeguard public health.